EVALUACIÓN SENSORIAL DE UNA BEBIDA TIPO CAPUCCINO A PARTIR DE LAS SEMILLAS FERMENTADAS Y NO FERMENTADAS DEL JACK FRUIT (Artocarpus heterophyllus Lam) - Arana Zurita, Jerley Izamar (2023)
This research sought to provide an innovative product to the market dedicated to the production of cappuccino-type drinks, adding Jack fruit in the form of flour as a substitute for chocolate. The physical-chemical and sensory characteristics of the drink were also evaluated, in the same way a DCA experimental design (Completely Random Design) was applied, where a total of 6 treatments with 3 replications (18 experimental units) were obtained. After completing the physical-chemical analyses, these results were recorded in the Infostat statistical software and in the same way, to verify the differences in means, a significance test called ´´Tukey¨ was applied. The sensory analysis was carried out by delivering a tasting sheet to students of the Agroindustry major; those results allowed us to identify which was the best treatment (T1: C40%; SNFJF 60% + milk + coffee). It should be noted that the production of cappuccinos should continue using Jack fruit flour as raw material due to the multiple benefits it has, among which are: fiber content, vitamins and minerals, antioxidants, and vegetable proteins. On the other hand, the methodology applied in the research is mentioned and likewise certain recommendations that may be useful for future research related to the production of cappuccino-type drinks.